2015
DOI: 10.1016/j.rmed.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Functional status at discharge and 30-day readmission risk in COPD

Abstract: Patients with COPD who were non-ambulatory within 24 h prior to discharge were at significantly greater risk of readmission compared to ambulatory patients. Functional status should be used to risk stratify patients for more intensive supportive interventions post discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 38 publications
2
32
0
1
Order By: Relevance
“…The risk of readmission increased with a greater number of previous emergency [19,32]. Previous COPD and non-COPD hospitalisations in the previous year also significantly increased the risk for 30-day readmission by 53% to 56% and 60% to 64%, respectively [38,39]. Consistent with other studies, GOTO et al [31] found that frequent exacerbators (defined as two hospitalisations in the past year) BOTTLE [21] GERSHON [32] GOTO [31] JACOBS [35] SHARIF [44] SIMMERING [45] TZY-CHYI YU [48] Overall (I 2 =95.4%, p=0.000) had a 2.5-fold increase in odds of readmission compared to non-frequent exacerbators.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…The risk of readmission increased with a greater number of previous emergency [19,32]. Previous COPD and non-COPD hospitalisations in the previous year also significantly increased the risk for 30-day readmission by 53% to 56% and 60% to 64%, respectively [38,39]. Consistent with other studies, GOTO et al [31] found that frequent exacerbators (defined as two hospitalisations in the past year) BOTTLE [21] GERSHON [32] GOTO [31] JACOBS [35] SHARIF [44] SIMMERING [45] TZY-CHYI YU [48] Overall (I 2 =95.4%, p=0.000) had a 2.5-fold increase in odds of readmission compared to non-frequent exacerbators.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Engagement in physical activity is a modifiable health behavior that affects COPD specific health outcomes independent of lung function 7374757677787980. People with COPD who have a high daily step count are at lower risk of dying than those with a low daily step count even after controlling for lung function (FEV 1 ) 747576.…”
Section: Chronic Obstructive Pulmonary Disease and Pulmonary Rehabilimentioning
confidence: 99%
“…An observational cohort study of 169 people with COPD who wore an accelerometer showed that those who were the least physically active had double the risk of acute exacerbations and six times the risk of hospital admission over a median follow-up of 16 months compared with those who walked the most 77. Patients who reported any moderate to vigorous physical activity (MVPA) had a lower risk of 30-day hospital readmission after an index admission for COPD compared with those who reported no MVPA 78. These studies of daily step count support the notion that every step walked can positively affect COPD outcomes.…”
Section: Chronic Obstructive Pulmonary Disease and Pulmonary Rehabilimentioning
confidence: 99%
“…The relationship between exacerbations of COPD and physical activity is complex and currently not well understood. Low activity levels are a strong predictor of future severe exacerbations; 6 10 however, physical activity is also known to be reduced during exacerbations. 11 13 Exacerbations are characterized by a worsening of the patient’s respiratory symptoms beyond the normal day-today variability; 14 however, there are a few studies published on exacerbation symptoms in relation to physical activity.…”
Section: Introductionmentioning
confidence: 99%